Low Birth Weight and Maternal and Neonatal Deaths are Complications of Systemic Lupus Erythematosus in Pregnant Pristane Induced Lupus Mice - Handono KALIM,; Kusworini HANDONO,; Mirza Zaka PRATAMA,; Sofi Nur FITRIA,; Vardian MAHARDIKA, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the relationship between systemic lupus erythematosus and pregnancy in pristane induced lupus mice model, including the pregnancy outcome for mothers and neonates. Materials and methods: Sixteen female Balb/c mice 6-8 week-old were separated into two groups: pristane induced lupus (PIL) mice group that received a single intraperitoneal injection of 0.5 ml of pristane and healthy control (HC) group that received phosphate-buffered saline injection. At one month after injection, all mice were mated with 8-10 week-old male Balb/c mice. All mice from both groups were observed for body weight and survival. On the day of births; number of neonates born, birth weight, and length of neonates were calculated. Neonates were also monitored for survival rate and their ages along the study. Results: There was no statistically significant difference in body weight before and after delivery, survival rate during pregnancy, number of neonates born, and gestational ages of mothers from both groups. Mothers began to die in the postpartum period. On third day after delivery, 0% of mothers from PIL group survived whereas 100% mothers from HC group survived (p=0.000). Of neonates born from PIL group, 15% survived at the end of fifth day after birth whereas 100% of neonates from HC group still survived (p=0.000). Neonates from PIL group also had significantly lower body weight and body length at birth compared to HC group (p=0.000 and p=0.000, respectively). Conclusion: Maternal and neonatal death, low birth weight, and low birth length are complications of systemic lupus erythematosus at pregnancy in pristane induced lupus mice model.